Rainbow graphs and semigroups - Protasova, K.D.; Provotar, Т.М. (Доповіді НАН України, 2012)
We give an algebraic characterization of rainbow graphs. A connected graph Γ is called rainbow
if there is a vertex coloring of Γ, which is bijective on the set of neighbors of each vertex of Γ. Отримано алгебраїчну характеризацiю веселкових графiв. Зв’язний граф Γ називається веселковим, якщо iснує розфарбування множини вершин Γ, що є бiєктивним на множинi сусiдiв кожної вершини Γ. Получена алгебраическая характеризация радужных графов. Связный граф Γ называется
радужным, если существует раскраска множества вершин Γ, биективная на множестве
соседей для каждой вершины Γ.